2016
DOI: 10.1371/journal.pone.0151304
|View full text |Cite
|
Sign up to set email alerts
|

Declining Trend of Hepatitis A Seroepidemiology in Association with Improved Public Health and Economic Status of Thailand

Abstract: Hepatitis A virus (HAV) is transmitted via the fecal-oral route from contaminated food or water. As part of the most recent survey of viral hepatitis burden in Thailand, we analyzed the current seroprevalence of HAV in the country and compared with data dating back to 1971. From March to October, 2014, a total of 4,260 individuals between one month and 71 years of age from different geographical regions (North = 961; Central = 1,125; Northeast = 1,109; South = 1,065) were screened for anti-HAV IgG antibody usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 21 publications
5
29
1
1
Order By: Relevance
“…This dynamic change confirms that over time, HAV enmity in Thailand has shifted from low to very low due to the improvement of sanitation and national economy [10]. The present study demonstrated the overall high HAV seropositivity in medical students in this era resembled that of the data in 1982 [1] when the vaccine was not available.…”
Section: Discussionsupporting
confidence: 82%
“…This dynamic change confirms that over time, HAV enmity in Thailand has shifted from low to very low due to the improvement of sanitation and national economy [10]. The present study demonstrated the overall high HAV seropositivity in medical students in this era resembled that of the data in 1982 [1] when the vaccine was not available.…”
Section: Discussionsupporting
confidence: 82%
“…The reduction in seroprevalence among subjects 15-29 years of age, as seen particularly in those 20-29 years of age, might be attributable in part to a decline in the circulation of HAV, because vaccination of children ultimately results in less exposure to the virus. However, it should be mentioned that natural infection has been declining with the rapid improvement in sanitation in recent years (Sa-nguanmoo et al, 2016;Franco et al, 2012), which will also have contributed to a decrease in anti-HAV seroprevalence in addition to the effects of vaccination. Nevertheless, the decline in seroprevalence will result in a higher proportion of population susceptible to HAV and should be of concern.…”
Section: Discussionmentioning
confidence: 99%
“…Changing government policy and increased trade and foreign investment have helped several countries such as Thailand, Singapore, Korea, Japan, and China to grow their economies during the last quarter century. This growth has been associated with an increase in healthcare expenditure and improvements in sanitation and hygiene levels, and increasing age at first HAV exposure (Sa-nguanmoo et al, 2016;Kiyohara et al, 2007). Korea is a good example.…”
Section: Discussionmentioning
confidence: 99%